2002
DOI: 10.1074/jbc.m201377200
|View full text |Cite
|
Sign up to set email alerts
|

AUF1 Is a bcl-2 A + U-rich Element-binding Protein Involved in bcl-2 mRNA Destabilization during Apoptosis

Abstract: We previously identified a conserved A ؉ U-rich element (ARE) in the 3-untranslated region of bcl-2 mRNA. We have also recently demonstrated that the bcl-2 ARE interacts with a number of ARE-binding proteins (AUBPs) whose pattern changes during apoptosis in association with bcl-2 mRNA half-life reduction. Here we show that the AUBP AUF1 binds in vitro to bcl-2 mRNA. The results obtained in a yeast RNA three-hybrid system have demonstrated that the 1-257-amino acid portion of p37 AUF1 (conserved in all isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 44 publications
2
86
0
1
Order By: Relevance
“…The binding of AUF1 to the ARE of bcl-2 is increased in apoptotic cells and inhibited by caspase inhibitors (Lapucci et al, 2002). Association of AUBPs with an ARE could promote or prevent the assembly of a decay complex necessary for the RNA turnover.…”
Section: Rate Of Rna Decay and Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of AUF1 to the ARE of bcl-2 is increased in apoptotic cells and inhibited by caspase inhibitors (Lapucci et al, 2002). Association of AUBPs with an ARE could promote or prevent the assembly of a decay complex necessary for the RNA turnover.…”
Section: Rate Of Rna Decay and Gene Expressionmentioning
confidence: 99%
“…Preliminary studies have shed some light on the biochemical mechanisms regulating the activity of some AUBPs (Laroia et al, 1999;Ming et al, 2001;Lapucci et al, 2002). The expression of each AUBP might be down-regulated by the use of antisense oligonucleotides, ribozyme, or siRNA , and if the AUBPs are classified as co-activators (e.g., AUF1 or TTP) or co-inhibitors (HuR), the rate of RNA degradation might be regulated accordingly.…”
Section: Aubps or The Exosome As The Targetmentioning
confidence: 99%
“…Both of these anti-apoptotic proteins have been shown to play a role in beta cell survival [22,40]. The effect of AUF1 on BCL2 may be mediated, at least in part, by direct association of the RNA-binding protein to the AU-rich elements present in the 3′-UTR of Bcl2 mRNA, resulting in messenger destabilisation [21,41]. Indeed, we observed that silencing of AUF1 results in a small but significant increase in Bcl2 mRNA stability.…”
Section: Discussionmentioning
confidence: 61%
“…It has been previously demonstrated that AUF1 isoforms can destabilise the mRNAs encoding the anti-apoptotic protein, BCL2 [21]. Western blotting analysis revealed that overproduction of p45 AUF1 results in a significant decrease in the production of BCL2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bcl-2 transcript contains an ARE and is rapidly degraded during apoptosis upon binding by the AUF1 protein (see below). 182 It has been reported that CDIR, a noncoding RNA overexpressed in lung cancer, 183 sequesters AUF1 away from Bcl-2 transcript, supporting Bcl-2 overexpression. 184 A recently identified oncoprotein, CaSM, appears to act by enhancing the stability of mRNAs including cyclin B1 by inhibiting 5 0 to 3 0 mRNA degradation.…”
Section: Mrna Stability and Cancermentioning
confidence: 99%